1 - Claude E. Ake and the Praxis of Knowledge Production in Africa - Arowosegbe, Jeremiah O. (Africa Development, 2021)
South-driven initiatives on endogenous knowledge production owe a great debt to Claude Ake. This article discusses the strengths and weaknesses of Ake’s account of the social sciences and knowledge production on Africa. It evaluates his legacies and presents him as one of the most fertile and influential voices within the social sciences community in Africa. Claude Ake, being a political scientist with an unusually broad intellectual formation and horizon, the article examines his production – over the last four decades – of a wide ranging body of works, which have been instructive, not only for their analytical acuity, methodological rigour and theoretical sophistication, but also for being remarkable products of a magisterial erudition, the creations of an exceptionally great mind, written with a deft and profound authority. The works also constitute a sigficant attempt to adapt the intellectual legacies of Marxist scholarship towards understanding the political economy and social history of contemporary Africa from a broadly critical perspective. The leitmotif in doing so is ‘to establish a specific relevance of studying Ake’s works’. Through an examination of the epistemological bases of policy, practice and theory in his corpus, this article establishes an important area within the social sciences in Africa positively affected by Ake’s intellectual involvement.